Evaluasi Penilaian Kinerja Perusahaan dengan Metode Refined Economy Value Added (REVA) pada PT. Sampoerna Agro, Tbk - Indika, Miki; Suharto; Wulandari, Novita (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
The aim of this study is to see financial performance of PT. Sampoerna Agro by using Refined Economy Value Added ( REVA) method. This study is conducted in PT. Sampoerna Agro from 2016 to 2020, this is descriptive study by using data from Bursa Efek Indonesia (BEI) official website from 2016 to 2020. Collecting data technique of this study is document analysis through official data website of BEI namely : www.idx.co.id and analyzing data tehnique of this study is descriptive analysis. The result of this study show that aveange calculating performance of PT. Sampoerna Agro from 2016-2020 by using refined Economy Value Added method gives the negative trend whic indicated the financial performance of the company is not enough where this company gave unexpected profit or return for the investor.